ANALISIS TINGKAT PENGETAHUAN, KEPUASAN DAN KEPERCAYAAN TERHADAP LOYALITAS PENGGUNA MUAMALAT DIGITAL ISLAMIC NETWORK DI KOTA MADIUN - Ari Rahmat Sugara (2023)
This study aims to determine and explain the effect of the level of knowledge, satisfaction, and trust on customer loyalty using the Muamalat Digital Islamic Network (MDIN) in the city of Madiun. This study uses quantitative methods. The population in this study is the user community of Muamalat Digital Islamic Network in Madiun. This study uses primary data as a data source with purposive sampling method as many as 175 respondents. Data analysis using SmartPLS with inner model and outer model test. The result of this research is the level of knowledge has a significant influence on customer loyalty. The level of knowledge is important because the respondent's answers indicate that the customer knows how to create an account either through the Muamalat DIN application or through Bank Muamalat KCP Madiun by coming in person. Satisfaction has a significant influence on customer loyalty. Satisfaction is obtained through customers who are comfortable when transacting using Muamalat DIN. Trust has a significant influence on customer loyalty. Customers believe that their deposit funds in Bank Muamalat are guaranteed safe. From the results of existing research, it is hoped that this research will be able to contribute to the PT. Bank Muamalat Tbk especially the Madiun branch office to continue to increase customer loyalty. The limitations of this study are that it only uses 3 independent variables and the scope of the research is only in the city of Madiun